EMOTIONAL STRESS FACED BY STUDENTS IN THE PROCESS OF LEARNING ACTIVITIES - Sodiqova Shohida Marhabayevna; Minavarkhujayeva Kamola Ilyos qizi; Minavarkhojayev Ravshankhuja Rakhmatkhuja ogli (Scholar Express Journal, 2023)
It consists in developing proposals and recommendations by determining the factors that cause emotional stress in students and their socio-psychological characteristics.
Keywords: students; emotional stress; emotional